Learning the Hard Way: The Effect of Violent Conflict on Student Academic Achievement - Tilman Brück; Michele Di Maio; Sami H. Miaari (Institute for the Study of Labor (IZA), 2014)
We study the effect of the Israeli-Palestinian conflict on the probability to pass the final high-school exam for Palestinian students in the West Bank during the Second Intifada (2000-2006). By exploiting within-school variation in the number of conflict-related Palestinian fatalities during the academic year, we show that the conflict reduces the probability to pass the final exam and to be admitted to the university. We also provide evidence of the heterogeneous effects of the conflict in terms of ability of the student and type of violent event the student is exposed to. Finally, we discuss possible transmission mechanisms explaining our main result.
Keywords: I20; O12; O15; F51; 330; academic achievement; high-school; Second Intifada; violent conflict; fatalities; West Bank; Palestine; Israel